Financing without collateral to small and medium enterprises in Klang Valley: a study of the firm characteristic / Ikmal Khairulluzin Jamil, Roza Hazli Zakaria and Azmah Othman - Jamil, Ikmal Khairulluzin; Zakaria, Roza Hazli; Othman, Azmah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
This paper attempts to understand the characteristic of small and medium enterprise (SME) firms in Klang Valley that received financing without collateral from the commercial lenders. SME located in Federal Territory of Kuala Lumpur (FT) and Selangor were selected as the population of the study. The legal status of the business entity, business sector the firm involved, using external advisor in conducting business, preparing a business plan, age of the firm and number of the employee owned by the firms, will be analysed and tabulated accordingly. The study combined two sampling methodologies, i.e. convenience and purposive to collect the data and at its level best, covering all 10 districts available in Selangor and FT. Accompanied by the close-ended questionnaire, an interview with 109 owner-manager (OM) was conducted for eighteen months. The data then analyzed using descriptive analysis before a conclusion was made.